2019
DOI: 10.1177/1178638819879444
|View full text |Cite
|
Sign up to set email alerts
|

Essential Mineral Intake During Pregnancy and Its Association With Maternal Health and Birth Outcomes in South East Queensland, Australia

Abstract: Micronutrient supplements are often recommended during pregnancy, yet their role and necessity remain poorly understood in the Australian population. This study aimed to determine the essential mineral intake of a population of pregnant women in South East Queensland and investigate the effects of supplements on their micronutrient status and birth outcomes. Women completing the Oral Glucose Tolerance Test at two South East Queensland hospitals between 180 and 210 days gestation provided fasting blood samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…The study by Caan et al [23] showed that the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) initiated 5-7 months before pregnancy resulted in an increase in birth weight by 131 g and length by 0.3 cm. Providing the right amount of essential elements with a diet or by supplementation can reduce the risk of fetal malformation and preterm birth [24], including multiple pregnancies-associated with a higher risk of perinatal complications [25]. These complications are likely to cause premature birth, miscarriage, hypotrophy of one or both fetuses, preeclampsia, fetal death, or fetal atrophy syndrome [26].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Caan et al [23] showed that the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) initiated 5-7 months before pregnancy resulted in an increase in birth weight by 131 g and length by 0.3 cm. Providing the right amount of essential elements with a diet or by supplementation can reduce the risk of fetal malformation and preterm birth [24], including multiple pregnancies-associated with a higher risk of perinatal complications [25]. These complications are likely to cause premature birth, miscarriage, hypotrophy of one or both fetuses, preeclampsia, fetal death, or fetal atrophy syndrome [26].…”
Section: Introductionmentioning
confidence: 99%
“…11 The implication of selenocysteine pathway suggests a potential benefit for further evaluation of the role of maternal Se status on PTB risk. The possible involvement of maternal Se concentration in PTB has also been suggested by previous epidemiological studies; [12][13][14][15][16] however, the sample sizes of these studies were usually small, or focus on a single geographic area and the results are not always consistent between studies. 17 18 In this study, we aimed to examine the association of maternal Se concentrations during pregnancy with PTB risk and gestational duration.…”
Section: Introductionmentioning
confidence: 77%
“…13 The Norwegian Mother, Father and Child Cohort study showed that higher Se intake from food was associated with increase in gestational length and decreased PTB risk. 15 Furthermore, the Maternal Health and Birth outcomes study in South East Queensland, Australia, suggested that dietary Se concentrations were significantly higher in women birthing beyond 41 completed weeks of gestation in that cohort. 14 However, there are also reports on Se metabolism with regard to gestational length that find contradicting results.…”
Section: Comparison With Other Studiesmentioning
confidence: 96%
“…a Low placental weight and control univariate (plasma); b low placental weight and control multivariate (plasma); c low placental weight and control univariate (urine); d low placental weight and control multivariate (urine); e SGA and control univariate (plasma); f SGA and control multivariate (plasma); g SGA and control univariate (urine); h SGA and control multivariate (urine); i preterm and control univariate (plasma); j preterm and control multivariate (plasma); k preterm and control univariate (urine); l preterm and control multivariate (urine) direction with vitamin and mineral consumption in any of the groups. When coupled with results from McAlpine et al (2019), which suggests that supplement use seems to have no significant influence on serum values of trace elements, it was determined that any consumption of supplements would not significantly influence elemental profiles [16]. Comparison of elemental concentrations collected from the Lyell McEwin cohort to those established in the literature can aid in the understanding of how the cohort reflects the current consensus of a normal population.…”
Section: Discussionmentioning
confidence: 98%
“…Blood plasma samples (20-fold dilution) and standards were prepared in a solution of 2.8% ammonia, 10% isopropanol, 0.2% Triton X-100, and 0.1% EDTA [13,16,17]; urine samples (20-fold dilution) and standards were prepared in a solution of 1% HNO 3 (sub-boiling distilled) [17]. Quality control standards at 10-100 μg/L were analysed every 12 samples.…”
Section: Sample Analysismentioning
confidence: 99%